Constructing Peace, Negotiating Gender: A Critical Discourse Analysis of Women-Led Websites in Indonesia and Malaysia - Athik Hidayatul Ummah; Muhamadaree Waeno (Faculty of Social Sciences and Humanities Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2025)
The role of women in peacebuilding has often been overshadowed by male-dominated discourse, particularly in contexts of extremist violence. Despite growing recognition of women’s contributions, their visibility and agency in digital peace initiatives remain underexplored. This research examines how women are constructed as active and reflective agents in peace discourse within cyberspace, negotiating socio-cultural and religious constraints. Data from this research were collected from two websites, Shebuildspeace.id (Indonesia) and Sistersinislam.org (Malaysia). Using a qualitative design, this research employed Norman Fairclough’s Critical Discourse Analysis (CDA) to analyze online narratives across textual, discursive, and socio-cultural dimensions. The findings reveal that both platforms foreground women’s agency in peacebuilding, emphasizing justice-oriented and inclusive practices while reflecting local norms and power structures. Shebuildspeace.id highlights women participation and practical grassroots peacebuilding initiatives, whereas Sistersinislam.org emphasizes women’s rights, equality, and social justice within a faith-based advocacy framework. These differences illustrate how women-led digital platforms construct peace and negotiate gender roles in line with their social, cultural, and contextual values. This research highlights the potential of digital media to expand women’s participation in peacebuilding and counter-extremism initiatives. Implications of this research include theoretical insights on public space and digital media, practical strategies for online peace initiatives, and policy recommendations supporting women-led peace and security agendas. Then, its limitations include the focus on only two platforms, which may not capture the full diversity of women-led digital peace discourse.